IMPLEMENTASI PROGRAM KARTU INDONESIA PINTAR DI SMK NEGERI 1 KAIDIPANG KABUPATEN BOLAANG MONGONDOW UTARA - ABRAM, ANDI ARNIDA ESA PUTRI; TULUSAN, FEMMY; LONDA, VERY (JURNAL ADMINISTRASI PUBLIK, 2018)
Abstract: As one of the programs in place, Smart Indonesia Card is a help from the government forunderprivileged / poor students, in the hope of reducing dropouts. Smart Indonesia Program is a priorityprogram of the President of the Republic of Indonesia Ir. Joko Widodo specially designed to help children frompoor families or unable to continue to get education services to finish secondary education or equivalent incooperation with the Ministry of Education and Culture (Kemendikbud), Ministry of Social Affairs (Kemensos)and Ministry of Religious Affairs (Kemenag). Through Indonesia's smart program, smart Indonesian cardshave been designed which is a card given to poor and vulnerable poor families whom they wish to send theirchildren to where the child is 6 - 21 years old for free. Already Many high schools in the district BolaangMongondow North, one of SMK Negeri 1 Kaidipang. Schools with this vocational base can help as soon aspossible the graduates to be able to find a job, but in education is certainly not far from the word cost.Approximately 45% of the students of SMK Negeri 1 Kaidipang who are classified as inadequate families havenot received assistance from the Smart Card Indonesia program and those who get the aid do not use the aidwith the best. What is the principle of the Smart Indonesia Program in permendikbud number 19 of the year2016 some less well done. Based on these facts then this research is very important considering the number ofchildren in SMK Negeri 1 Kaidipang who need help to take education. A policy / program is created in responseto a problem, which is to solve, reduce, prevent problems from being solved. However, the implementation of aprogram will not be far from the word problem to be faced in the field, there will be various obstacles to realizethe ideals that have been designed. The study aims to explain the implementation of the Smart Card Indonesiaprogram at SMK Negeri 1 Kaidipang Bolaang Mongondow Utara District.Keywords : Implementation, program Indonesian smart, smart Indonesian card